The Role of GM130 in Nervous System Diseases - Huang, Bei; Li, Xihong; Zhu, Xiaoshi (Frontiers in Neurology, 2021)
Golgi matrix protein 130 (GM130) is a Golgi-shaping protein and located on the cis surface of the Golgi apparatus (GA). It is one of the most studied Golgin proteins so far. Its biological functions are involved in many aspects of life processes, including mitosis, autophagy, apoptosis, cell polarity and directed migration at the cellular level, as well as intracellular lipid and protein transport, microtubule formation and assembly, lysosome function maintenance, glycosylation modification. Mutation inactivation or loss of expression of GM130 has been detected in patients with different diseases. GM130 plays an important role in the development of the nervous system, but the studies on it are limited. This article reviewed the current research progress of GM130 in nervous system diseases. It summarized the physiological functions of GM130 in the occurrence and development of Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), microcephaly (MCPH), sepsis associated encephalopathy (SAE) and Ataxia, aiming to provide ideas for the further study of GM130 in nervous system disease detection and treatment.